2019
DOI: 10.1108/hff-08-2019-0620
|View full text |Cite
|
Sign up to set email alerts
|

Melting heat transfer of a non-Newtonian phase change material in a cylindrical vertical-cavity partially filled porous media

Abstract: Purpose This paper aims to investigate melting heat transfer of a non-Newtonian phase change material (PCM) in a cylindrical enclosure-space between two tubes using a deformed mesh method. Design/methodology/approach Metal foam porous layers support the inner and outer walls of the enclosure. The porous layers and clear space of the enclosure are filled with PCM. The natural convection effects during the phase change are taken into account, and the governing equations for the molten region and solid region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The results showed that the presence of carbon nanotubes reduces and increases the heat transfer rate and the melting time, respectively. Ghalambaz et al (2019aGhalambaz et al ( , 2019b examined the impact of a layer of metal foam on the phase change heat transfer of a PL non-Newtonian PCM in a cylindrical enclosure. The metal foam was an isotropic porous aluminum that could be placed in different locations in the enclosure.…”
Section: Melting Process Of Pcmmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the presence of carbon nanotubes reduces and increases the heat transfer rate and the melting time, respectively. Ghalambaz et al (2019aGhalambaz et al ( , 2019b examined the impact of a layer of metal foam on the phase change heat transfer of a PL non-Newtonian PCM in a cylindrical enclosure. The metal foam was an isotropic porous aluminum that could be placed in different locations in the enclosure.…”
Section: Melting Process Of Pcmmentioning
confidence: 99%
“…The Nusselt number was examined for the surface of the hot tube. The local effective Nusselt number for the porous medium on the considered surface was defined according to the base fluid (Ghalambaz et al , 2019a, 2019b): …”
Section: Model Description and Formulationmentioning
confidence: 99%
“…Recently, Selimefendigil and Chamkha [24] found significant changes in the average Nusselt number, which are obtained by varying the location of the porous medium. Ghalambaz et al [25] and Ghalambaz et al [26] investigated the thermal performance of nanoencapsulated phase change material suspension in the composite enclosure. Recently, Aly and Alsedais [27] concluded that at lower Darcy parameters, the existence of a porous sheet in the right region inhibits the suspension flow in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Ayoubloo et al (2019) examined the natural convection of pseudo-plastic fluids moving through a cylindrical vertical cavity. Ghalambaz et al (2019) and Ayoubloo et al (2019) scrutinized the heat transfer mechanism during melting in a porous medium. Mishra et al (2019) scrutinized the buoyancy-driven flow with electro-magnetohydrodynamic (EMHD) and chemical effects over a stretching surface using a nonlinear Darcy model.…”
Section: Introductionmentioning
confidence: 99%